The Bibliometric Analysis of Interventions in English Literacy Difficulties of Primary School Students with Dyslexia - Wahyuni, Sri; Dafit, Febrina; Asnawi, Asnawi; Etfita, Fauzul (Journal of Teaching and Learning, 2026)
This study aims to map the research landscape on English literacy difficulties and interventions among primary school students with dyslexia using a bibliometric approach. Data were retrieved from the Scopus database using targeted keywords, resulting in 63,184 documents. After applying filters for publication year (2020–2025), subject area (social sciences), language (English), and open-access status, a final dataset of 1492 relevant articles was obtained. Following this, the analysis was subsequently performed in RStudio using Biblioshiny and visualized with VOSviewer. The results indicate a substantial decrease in annual growth in publications, despite high levels of author involvement and collaborative endeavours. The United States and the United Kingdom dominate in production and citation impact, and notable journals, scholars, institutions, and nations are among the key contributors. Likewise, four major research areas emerged from the thematic cluster analysis, including foundational literacy skills, learning disorders in school settings, speech and communication difficulties, and educational psychology aspects such as self-esteem. Findings from this study stress the need for early, organized, and comprehensive interventions for children with dyslexia, which has several facets. To close the gap in dyslexia-related scholarship worldwide, it also highlights the need for more inclusive, geographically diverse research collaborations.